2022
DOI: 10.1590/0100-6991e-20223204edit01
|View full text |Cite
|
Sign up to set email alerts
|

Women Representation in Surgical Specialties: Reflections about Gender Equity after the 34th Brazilian Surgical Conference

Abstract: In September 2021, the 34th Brazilian Surgical Conference hosted the “Panel: Women in Surgery” - the only session in the event solely composed of female speakers. Although gender inequities in surgery are well recognized in the international literature, the panel portrayed how distant we are from the desired equity in our country. In addition, the session emphasized the need to broaden the debate and identify the mechanisms for greater inclusion and maintenance of women in the surgical career. In this editoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…In a combined approach by anatomists and surgeons, courses including biomechanics, advanced dissection, surgical approaches, casts and implants, and sports medicine facilitated the appreciation of potential career options in orthopedics, while fostering professional skills during medical training (Klima et al, 2017). This is particularly valuable in light of the predicted demand of surgical disciplines for young physicians (Grover et al, 2009), including the underrepresentation of female surgeons (e.g., Viana et al, 2022), particularly in orthopedic surgery (Rohde et al, 2016). Kim and co‐workers (2015) reported that 50% of surgical residents preferred a multimodal learning style and for 64%, the preferences included a kinesthetic aspect, similar to a study in Saudi Arabia, where male and female dental students had a unimodal preference for kinesthetic learning (Hashem, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In a combined approach by anatomists and surgeons, courses including biomechanics, advanced dissection, surgical approaches, casts and implants, and sports medicine facilitated the appreciation of potential career options in orthopedics, while fostering professional skills during medical training (Klima et al, 2017). This is particularly valuable in light of the predicted demand of surgical disciplines for young physicians (Grover et al, 2009), including the underrepresentation of female surgeons (e.g., Viana et al, 2022), particularly in orthopedic surgery (Rohde et al, 2016). Kim and co‐workers (2015) reported that 50% of surgical residents preferred a multimodal learning style and for 64%, the preferences included a kinesthetic aspect, similar to a study in Saudi Arabia, where male and female dental students had a unimodal preference for kinesthetic learning (Hashem, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…There is also an impact of this subrepresentation by Gender of Recognition Award Recipients from Gastroenterology and Hepatology Professional Societies (6) , which relegates women to a less prominent position within scientific events. While this low representation is a recurring issue in other areas of medicine such as surgery, neurology, and anesthesia (7) , there is currently a gap in the literature regarding the underrepresentation of women in hepatology events. To create a strong community with good career progression for its members, the scientific potential of the female contingent cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Embora isso ocorra, evidências mostram que equipes com maior representação feminina apresentam melhores resultados clínicos e cirúrgicos. 8 Outros desafios incluem equívocos sobre a falta de força física das mulheres, a longa duração da formação necessária, o rigor físico e emocional durante a residência e o estigma de gênero profundamente enraizado que desencoraja as mulheres a seguirem carreiras cirúrgicas.…”
Section: Metodologiaunclassified